Preventive Analysis of Maintenance On Centrifugal Pumps Using The Mean Method Time Between Failure (MTBF) and Mean Time To Repair (MTTR) - Ardian Saputra; Erwen Martianis (International Journal of Science and Environment (IJSE), 2026)
Centrifugal pumps are essential equipment in fluid distribution systems that operate continuously, so they have the potential to suffer damage that can reduce the reliability of the system. This study aims to analyze the damage and effectiveness of centrifugal pump maintenance using the Preventive Maintenance Analysis method on centrifugal pumps using the Mean Time Betwwn Failure (MTBF) and Mean Time To Repair (MTTR) methods. The MTBF value is used to determine the reliability level of the pump, while the MTTR is used to evaluate the efficiency of the repair time. The results of the analysis show that a high MTBF value indicates good pump reliability, while a low MTTR value indicates an efficient repair process. Based on the results of the study, it can be concluded that the implementation of planned and reliability-based maintenance is able to reduce downtime and improve the performance and service life of centrifugal pumps. This research is expected to be a reference in the preparation of a more effective and optimal pump maintenance strategy.